Criticism, art and theory in 1970s Britain : the critical war - Charlesworth, J. J. (New York, NY : Routledge, 2024)
"A critical study of the life of art criticism in the 1970s, this volume traces the evolution of art and art criticism in a pivotal period in post-war British history. JJ Charlesworth explores how art critics and the art press attempted to negotiate new developments in art, faced with the challenges of conceptualism, alternative media, new social movements and radical innovations in philosophy and theory. This is the first comprehensive study of the art press and art criticism in Britain during this pivotal period, seen through the lens of its art press, charting the arguments and ideas that would come to shape contemporary art as we know it today. This book would be of interest to scholars working in art history, British cultural history, and history of journalism"--
Towards the new art : the artist as theorist in Studio International, 1967-1970 -- Art criticism in the alternative press 1971-73 -- Looking for the subject : Peter Fuller and the new critics, 1970-76 -- Young conservatives : from ONE to Artscribe, 1973-1976 -- The first 'crisis of criticism', 1976-79.
Keywords: Art criticism -- Great Britain -- History -- 20th century; ART / Criticism; ART / History / Contemporary (1945-); LITERARY CRITICISM / European / English, Irish, Scottish, Welsh